THE EFFECT OF LOCUS OF CONTROL, STUDENTS PERCEPTIONS OF TEACHER TEACHING METHODS AND PARENTS CONCERN TOWARD ACCOUNTING LEARNING ACHIEVEMENT - Melinda Dhian Kusuma; Rr. Indah Mustikawati (Jurnal Pendidikan Akuntansi Indonesia, 2017)
This research aimed to know the effect of Locus of Control, Students Perceptions of Teacher Teaching Methods and Parents Concern toward Accounting Learning Achievement. Subject of this research was students of XI IPS SMA Negeri 2 Sleman Academic Year 2016/2017 about 63. Data collection was carried out by documentation and questionnaire. Test of analysis consist of linearity test, multicollinearity test, simple regression test (hypothesis 1,2 and 3) and multiple regression test (hypothesis 4). Research results: 1) there was a positive effect of Locus of Control toward Accounting Learning Achievement, 2) there was a positive effect of Student Perceptions of Teacher Teaching Methods toward Accounting Learning Achievement, 3) there was a positive effect of Parents Concern toward Accounting Learning Achievement ,4) there was a positive effect of Locus of Control, Student Perceptions of Teacher Teaching Methods and Parents Concern toward Accounting Learning Achievement.Keywords: Locus of Control, Student Perceptions, Teacher Teaching Methods, Parents Concern, Accounting Learning Achievement.